Capabilities of fast data acquisition with microsecond time resolution in inductively coupled plasma mass spectrometry and identification of signal artifacts from millisecond dwell times during detection of single gold nanoparticles. Issue 1 (14th August 2015) - Strenge, I.; Engelhard, C.
Abstract : In this paper, a home-built DAQ featuring microsecond time resolution is used to demonstrate advantages of fast data acquisition and to uncover potential artifacts in single-particle ICP-MS. Abstract : In inductively coupled plasma mass spectrometry (ICP-MS), short transient signals originating from individual nanoparticles are typically recorded in a time-resolved measurement with reduced dwell times in the millisecond time regime. This approach was termed single-particle ICP-MS in the past and used for particle counting and sizing but is not without limitations. In this work, a home-built data acquisition unit (DAQ) specifically tailored to the needs of single-particle ICP-MS applications was developed to study and alleviate some of these limitations. For best comparison, data were acquired simultaneously with both techniques. Each experiment was carried out as a conventional time-resolved measurement, while the DAQ directly probed the instrument's detection circuitry. Our DAQ features dwell times as low as 5 μs during continuous data acquisition and can be operated for virtually unlimited measurement time. Using a time resolution much higher than the typical duration of a particle-related ion cloud, the probability of measurement artifacts due to particle coincidence could be significantly reduced and the occurrence of split-particle events in fact was almost eliminated. Moreover, a duty cycle of 100% of the counting electronics improves the method's accuracy compared to the acquisition system of currently available ICP-Q-MS instruments. Fully time-resolved temporal profiles of transient signals originating from single gold nanoparticles as small as 10 nm are presented. The advantages and disadvantages of millisecond versus microsecond dwell times are critically discussed including measurement artifacts due to particle coincidence, split-particle events, and particle number concentration.